Designing A Secured Framework for the Steganography Process Using Blockchain and Machine Learning Technology - Chaudhary, Ayushi; Sharma, Ashish; Gupta, Neeraj (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Recently, Blockchain technology has become popular. Through a highly secure, decentralized system enabled by this technology, anyone can transact securely without the need for a middleman. Machine learning can assist in addressing many of the constraints that Blockchain-based systems have in addition to their own potential. Machine learning and Blockchain technology can be combined to produce effective and practical outcomes. The infrastructures, resources, end devices, and applications in communications and networking systems are becoming increasingly more complicated and heterogeneous recently due to the rapid growth of information and communication technology. Additionally, the enormous amount of data and numerous endpoints could pose significant security, privacy, delivery of services, and network management difficulties. The combination consideration of Blockchain and Machine Learning is necessary to accomplish decentralized, secure, intelligent, and effective network operation and management (ML). This article will explain Blockchain technology and examine how machine learning capabilities can be combined with a Blockchain-based system to build a stego cryptography to secure the data during communication over the network.